Indonesian Euphorbiaceae: Ethnobotanical Survey, In Vitro Antibacterial, Antitumour Screening and Phytochemical Analysis of Euphorbia atoto - Dyke Gita Wirasisya; Annamária Kincses; Lívia Vidács; Nikoletta Szemerédi; Gabriella Spengler; Anita Barta; I Gde Mertha; Judit Hohmann (Plants, 2023)
Indonesia is among the countries with the most significant biodiversity globally. Jamu, the traditional medicine of Indonesia, predominantly uses herbal materials and is an integral component of the Indonesian healthcare system. The present study reviewed the ethnobotanical data of seven Indonesian Euphorbiaceae species, namely Euphorbia atoto, E. hypericifolia, Homalanthus giganteus, Macaranga tanarius, Mallotus mollissimus, M. rufidulus, and Shirakiopsis indica, based on the RISTOJA database and other literature sources. An antimicrobial screening of the plant extracts was performed in 15 microorganisms using the disk diffusion and broth microdilution methods, and the antiproliferative effects were examined in drug-sensitive Colo 205 and resistant Colo 320 cells by the MTT assay. The antimicrobial testing showed a high potency of M. tanarius, H. giganteus, M. rufidulus, S. indica, and E. atoto extracts (MIC = 12.5–500 µg/mL) against different bacteria. In the antitumour screening, remarkable activities (IC50 0.23–2.60 µg/mL) were demonstrated for the extracts of H. giganteus, M. rufidulus, S. indica, and E. atoto against Colo 205 cells. The n-hexane extract of E. atoto, with an IC50 value of 0.24 ± 0.06 µg/mL (Colo 205), was subjected to multistep chromatographic separation, and 24-methylene-cycloartan-3β-ol, jolkinolide E, tetra-tert-butyl-diphenyl ether, α-tocopherol, and β-sitosterol were isolated.